Response of understorey plant communities and traits to past land use and coniferous plantation. Issue 3 (21st January 2017) - Bergès, Laurent; Feiss, Thomas; Avon, Catherine; Martin, Hilaire; Rochel, Xavier; Dauffy‐Richard, Emmanuelle; Cordonnier, Thomas; Dupouey, Jean‐Luc
Abstract: Questions: How did past land use and conifer plantation affect understorey plant communities? What plant traits explain understorey vegetation response to agricultural past land use and coniferous plantation? Location: Forest of Orléans (50 000 ha), Loiret, north‐central France. Methods: Canopy cover, herb layer composition, litter and soil properties were measured in 80 100 m 2 plots sampled in plantations of Pinus sylvestris or P. nigra vs natural regenerations of Quercus petraea and Q. robur along a gradient of forest continuity (using historical maps and aerial photos from 1840, 1949 and 2006). We related 15 plant traits to past land use and tree species using RLQ and fourth‐corner analyses. Results: The magnitude of past land use effect largely exceeded that of coniferous plantation. Post‐agricultural forests, even 150 yr after afforestation, differed from ancient forests in soil properties (thinner humus layer, higher P content, higher pH and lower C/N ratio) and plant traits. Ancient forests hosted more forest core species, stress‐tolerant, competitive species and bryophytes, but fewer ruderals, annuals/biennials, shrubs and trees and nutrient‐demanding species, and had lower SLA and higher LDMC. Conifer plantations had a thicker humus layer, lower pH and higher C/N ratio than deciduous forests, and hosted more light‐demanding species but less forest core species. Importantly, differences in soil and plant traits between conifer plantations and naturally regenerated deciduous stands were discernible in both recent and ancient forests, indicating that tree species lastingly influence ecosystem functioning. Conclusions: Past land use and coniferous plantation resulted in different understorey plant communities and traits under pine plantations and naturally regenerated oak stands. These differences were driven through soil acidification, litter decomposition rate, light conditions, canopy development, soil disturbance, stand management and dispersal and recruitment limitations. Coniferous plantations slowed down the recovery of post‐agricultural forests to ancient deciduous forest conditions. Applying natural regeneration and favouring native deciduous tree species thus helps recreate or maintain ancient forest plant communities. Abstract : We investigated to what extent conifer plantation modified the composition and the traits of understory plant communities in recent and ancient forests, compared with naturally‐regenerated deciduous tree species. Conifer plantation resulted in a long‐lasting distinct taxonomic and functional trait composition. Coniferous plantation slowed down the recovery of post‐agricultural forests towards ancient deciduous forest conditions.